Profile of Out-of-School Children in the Philippines - Jose Ramon G. Albert; Andre Philippe Ramos; Francis Mark A. Quimba; Jocelyn P. Almeda (Philippine Institute for Development Studies (PIDS), 2012)
The Philippines committed to Millennium Development Goals and Education for All (EFA) targets that include universal primary education. However, various data sources, including the Department of Education's Basic Education Information System and household surveys conducted by the National Statistics Office, suggest that in 2008, a considerable magnitude of children were not in school. A description of these children is provided here as well as that of children who are at risk of dropping out of primary and secondary levels of education. Reasons for children not being in school are discussed, together with the results of an econometric model that identifies correlates of nonattendance in school.
Keywords: 330; Philippines; school attendance; school participation; net enrollment rate (NER); out-of-school children; dropouts; Kinder; Bildungschancen; UN-Entwicklungsziele; Philippinen